Assessing Teaching Interns’ Anxiety and Self‑Efficacy Following the COVID‑19 Pandemic - Gutierrez, Jr., Ernesto A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The COVID-19 pandemic imposed unprecedented disruptions in educational systems, significantly affecting the practicum experiences of teaching interns. This study examined the post-pandemic levels of teaching anxiety and teaching self-efficacy among pre-service teachers at Cavite State University Naic. Utilizing a descriptive-correlational research design, data were collected from 92 Bachelor of Elementary and Secondary Education interns through the Teaching Anxiety Scale (TAS) and Teaching Self-Efficacy Scale (TSES). Results indicated that respondents exhibited generally high levels of teaching self-efficacy, particularly in classroom management and instructional strategies, despite reporting moderate and varied levels of teaching anxiety. A weak yet statistically significant positive correlation (r = 0.292, p < 0.01) was found between self-efficacy and teaching anxiety. Regression analysis further revealed that teaching anxiety significantly predicted teaching self-efficacy (β = 0.254, p = 0.014). These findings highlight the need for structured interventions—including mentorship, stress management, and technology training—to support the psychological and pedagogical preparedness of future educators.